If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-g/4+1=0
We multiply all the terms by the denominator
-g+1*4=0
We add all the numbers together, and all the variables
-1g+4=0
We move all terms containing g to the left, all other terms to the right
-g=-4
g=-4/-1
g=+4
| 6w-16=32 | | 66x=6 | | +8x-15x=+29-15 | | 15(x+3)=9(x+3) | | 79m+19.99=219.86 | | 3k=51 | | 12x=5/4x+3 | | 8.2x-2.1=109.8 | | 7(6-x)=6 | | 8.2x-3.5x=9.4 | | 4,005=45(x+30) | | 5/6d=-2.5 | | y-0.5+y-0.5+y-0.5+4.5=y+1+y+1 | | 4,005=30(x+30) | | 2h+9=5h+1+6h | | |6-2x|=24 | | 3x+13.2=2.6 | | -16=3m-4 | | 9.7=-5h-15.3 | | 4=-6-x | | Y=4.25x | | d=3(7)-7+-2 | | -0.54x+0.34x=5.6 | | 7-4f=11 | | 2(x-1)=10;x | | k/8-1=3 | | x+x+x+14.7+x+14.7=113.4 | | z=52 | | -3x+1-x=-5-2x | | -3x+1-x=4+5 | | 6v+8=-46v | | 4(x+3)=4(2x-2) |